Analisis Hidrologi, Hidrolika untuk Penampang Persegi Panjang, Trapesium dan Segitiga Berdasarkan Pedoman Perencanaan Saluran Jalan Departemen PU (Pd.T-02-2006.B) - Muhammad Ridha; Amalia, Amalia; Sriana, Tety (Universitas Iskandar Muda, 2025)
The geometric shapes of various types of drainage commonly used are: rectangular, usually used in urban areas; trapezoidal, used in agricultural areas for irrigation; and triangular. This study was conducted in Pieyeung Datu Village, Montasik Subdistrict, Aceh Besar Regency. For hydrological data (rainfall), rainfall data from Aneuk Glee Village, Aceh Besar Regency was used for station 1 and Meunasah Baro Village, Seulimeum Subdistrict, Aceh Besar for station 2. The distribution and suitability tests followed the Log Pearson Type 3 distribution. The concentration time analysis yielded a result of Tc = 14.096 minutes, and the 5-year return period discharge (Q5) using the modified rational method was 0.25 m3/second. The long channel has a channel discharge capacity of 0.276 m3/second, a flow velocity in channel 1 of 380 m/s, the trapezoidal channel has a discharge of 0.260 m³/s with a flow velocity of 1.48 m/s, and the triangular channel has a discharge of 0.293 m³/s and a flow velocity in the channel/design velocity of 1.46 m/s. For the Budget Plan (RAB), it was found that the triangular channel had the lowest cost, amounting to Rp. 221,937,500.00, followed by the trapezoidal channel at Rp. 248,235.00, and the rectangular channel with the highest cost, amounting to Rp. 295,020,000.00.